Markups and inflation in oligopolistic markets: Evidence from wholesale price data - Patrick Alexander; Lu Han; Oleksiy Kryvtsov; Ben Tomlin (Bank of Canada, 2024)
We study how the interaction of market power and nominal price rigidity influences inflation dynamics. We formulate a tractable model of oligopolistic competition and sticky prices and derive closed-form expressions for the pass-through of idiosyncratic and common cost shocks to firms' prices. Using unpublished micro data for Canadian wholesale firms, we estimate that the pass-through of idiosyncratic costs is incomplete at 70% and independent of the degree of sector-price-stickiness. The pass-through of common costs declines with price stickiness, from nearly complete in flexible-price sectors to below 70% in sectors with the stickiest prices. An increase in the degree of sector or firm market power reduces the pass-through of both types of cost shocks. These estimates imply a degree of strategic complementarity that lowers the slope of the New Keynesian Phillips curve by 30% in a one-sector model and by 74% in a multi-sector model.
Keywords: D43; E31; L13; L81; 330; Firm dynamics; Inflation and prices; Market structure and pricing; Monetary policy transmission